2002
DOI: 10.1046/j.1532-5415.2002.50020.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Placebo‐Controlled Study of Oral Vitamin B12 Supplementation in Older Patients with Subnormal or Borderline Serum Vitamin B12 Concentrations

Abstract: Cyanocobalamin supplementation of 50 microg but not 10 microg daily produced a significant increase in serum vitamin B12. This result has implications for the management of patients with subnormal or borderline serum vitamin B12 concentrations and for food fortification with vitamin B12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 11 publications
(25 reference statements)
4
87
2
2
Order By: Relevance
“…Although a number of studies in healthy populations and in patients have investigated the effect of various doses of folic acid supplementation in lowering tHcy, few have examined the independent effects of vitamin B 12 . In those studies that have administered low-dose vitamin B 12 as a separate treatment, the response of vitamin B 12 biomarkers was the primary outcome and the tHcy response was measured as a secondary objective (21,22) . Furthermore, the study populations were selected for mild vitamin B 12 deficiency and were not pretreated with folic acid before vitamin B 12 supplementation.…”
Section: Vitamin B 12mentioning
confidence: 99%
“…Although a number of studies in healthy populations and in patients have investigated the effect of various doses of folic acid supplementation in lowering tHcy, few have examined the independent effects of vitamin B 12 . In those studies that have administered low-dose vitamin B 12 as a separate treatment, the response of vitamin B 12 biomarkers was the primary outcome and the tHcy response was measured as a secondary objective (21,22) . Furthermore, the study populations were selected for mild vitamin B 12 deficiency and were not pretreated with folic acid before vitamin B 12 supplementation.…”
Section: Vitamin B 12mentioning
confidence: 99%
“…Randomized trials of the effect of lowering tHcy with B-vitamins (folic acid, B12 and, to a lesser extent, B6) on cognitive decline minimize confounding and reverse causality but have produced conflicting or equivocal results. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The 2 trials that reported a benefit from lowering tHcy did so in subjects with elevated tHcy. 19,27 In view of the uncertainty of the effect of lowering tHcy with B-vitamins on cognition, we aimed to assess, in a prespecified study, whether B-vitamin treatment would reduce the incidence of new cognitive impairment among cognitively unimpaired individuals with recent stroke or transient ischemic attack (TIA) of the brain enrolled in the VITAmins TO Prevent Stroke (VITATOPS) trial, 29,30 and whether the effect of B-vitamins on cognitive function may be augmented in, or limited to, participants with elevated tHcy.…”
mentioning
confidence: 99%
“…With test doses of 10 μg and 50 μg B 12 per day, only the 50 μg dose produced a significant increase in serum B 12 concentration. [13] In another study, 600 μg B 12 /day, 300 times greater than the recommended dietary allowance of 2 μg/day, was needed to normalise low serum B 12 and raised methylmalonic acid. [14] Results in patients with food B 12 malabsorption show similar variation, one study showing increased serum B 12 following a daily dose of 5.9 μg, [15] while in another 250 -1 000 μg/day was required to have any effect.…”
Section: Fff and The Implications For Patients With Vitamin B 12 Defimentioning
confidence: 99%